STRATEGI MANAJEMEN TAHFIDZUL QUR’AN DI MI UNGGULAN MASJID BESAR JABALUL KHOIR PURWODADI: - - Mutia Al Khusna; A Umar; Budi Utomo (Jurnal Manajemen Pendidikan, 2026)
The study was motivated by the importance of systematically managing Qur’an memorization programs in islamic educational institutions to maintain the quality of students’ memorization and uphold trust in madrasahs. The MI Unggulan Masjid Besar Jabalul Khoir Purwodadi is a madrasah that has made the Qur’an memorization program its flagship initiative. However, following the Covid-19 pandemic, there has been adecline in the quality of memorization due to a lack of consistency in review sessions. This study aims to analyze Qur’an meorization management strategies, encompassing program planning, implementation, and evaluation. This study employs a descriptive qualitatitve approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The result of the study indicate that: (1) program planning is carried out systematically through problem identification, goal setting, schedulling, selection of human resources, and participatory evaluation planning, (2) program implementation was carried out through daily recitation, rputine review, and support from teachers and parents, (3) evaluation was conducted periodically through recitation, tasmi’ exams, and parental monitoring. This strategy proved effective in improving the quality ofmemorization and maintaining trust in the madrasah.